PENGEMBANGAN MEDIA ANIMASI BERBASIS WEBSITE PADA MATERI SISTEM REPRODUKSI MANUSIA DI SMP PARAMARTA SEPUTIH BANYAK - Nabilla Nur Azizah; HRA Mulyani; Anak Agung Oka (EDUBIOLOCK, 2026)
The endeavor was undertaken to craft an instructional animation platform accessible via a website and to appraise its capacity in augmenting pupils’ cognition regarding the human reproductive mechanism. The procedure implemented adhered to the Research and Development (R&D) paradigm, employing the ADDIE sequence (Analysis, Design, Development, Implementation, Evaluation). Participants enlisted in this endeavor encompassed eighth-grade learners at SMP Paramarta Seputih Banyak. Insights from the pilot phase revealed that the constructed medium exhibited remarkable feasibility, attaining validation rates of 98% from domain authorities and 86% from visual-media evaluators. Subsequent refinements were applied before the instrument was administered to a cohort of ten students, producing a notable elevation in mastery of concepts, denoted by a mean N-Gain score of 0.73, classified as elevated. The pupils’ appraisal of the medium was exceptionally affirmative, averaging 93.25%, thereby situating it within the “extremely feasible” classification. In summation, the animation-based website medium has been corroborated to proficiently foster enhanced comprehension of the human reproductive apparatus among learners.